2018
DOI: 10.1162/ling_a_00271
|View full text |Cite
|
Sign up to set email alerts
|

Unaccusativity in Sentence Production

Abstract: Linguistic analyses suggest that there are two types of intransitive verbs: unaccusatives, whose sole argument is a patient or theme (e.g., fall), and unergatives, whose sole argument is an agent (e.g., jump). 1 Past psycholinguistic experiments suggest that this distinction affects how sentences are processed: for example, it modulates both comprehension processes ( Bever and Sanz 1997 , Friedmann et al. 2008 ) and production processes ( Kegl 1995 , Kim 2006 , M. Lee and Thompson 2004 , J. Lee and Thompson 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 24 publications
3
25
1
Order By: Relevance
“…Lee and Thompson, 2011;Momma et al, 2016Momma et al, , 2017Momma et al, , 2018, some of this research also finds that typical subjects (i.e., those in transitive and unergative sentences) do not. In particular, Momma et al (2016Momma et al ( , 2018. have found that the time it takes to start uttering a sentence increases when there is semantic interference affecting the verb, but this only happens for sentences where the DO precedes the verb (in Japanese; Momma et al, 2016), or when the subject is semantically more related to a DO than to a typical subject (i.e., for English unaccusatives; Momma et al, 2018) 2 , but not when the first constituent in the sentence is a typical sentence subject.…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…Lee and Thompson, 2011;Momma et al, 2016Momma et al, , 2017Momma et al, , 2018, some of this research also finds that typical subjects (i.e., those in transitive and unergative sentences) do not. In particular, Momma et al (2016Momma et al ( , 2018. have found that the time it takes to start uttering a sentence increases when there is semantic interference affecting the verb, but this only happens for sentences where the DO precedes the verb (in Japanese; Momma et al, 2016), or when the subject is semantically more related to a DO than to a typical subject (i.e., for English unaccusatives; Momma et al, 2018) 2 , but not when the first constituent in the sentence is a typical sentence subject.…”
Section: Introductionsupporting
confidence: 53%
“…Additionally, while some authors have found that the verb's internal arguments [i.e., direct objects (DOs) and subjects of unaccusative verbs] depend on verb retrieval for their processing (J. Lee and Thompson, 2011;Momma et al, 2016Momma et al, , 2017Momma et al, , 2018, some of this research also finds that typical subjects (i.e., those in transitive and unergative sentences) do not. In particular, Momma et al (2016Momma et al ( , 2018.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Prior work in production has tended to focus on declarative, transitive sentences in English, where the subject of the sentence is also the linearly initial argument (cf. Momma et al, 2018). The current work uses English object wh-questions, where the object linearly precedes the subject (e.g.…”
mentioning
confidence: 99%